Characterization of thin carbon films produced by the magnetron sputtering technique - Costa E Silva, Danilo Lopes; Pires Kassab, Luciana Reyes; Martinelli, Jose Roberto; Dos Santos, Antonio Domingues; Lima Ribeiro, Sidney José [UNESP]; Dos Santos, Moliria Vieira [UNESP] (FapUNIFESP (SciELO), 2016)
Thin carbon films containing both amorphous and crystalline structures were produced by RF magnetron sputtering. The depositions of the carbon films were performed on Co buffer layers previously deposited on c-plane (0001) sapphire substrates. The thin carbon films were characterized by high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), Raman spectroscopy, energy dispersive X-ray spectroscopy (EDS), and field emission scanning electron microscope (FEG-SEM). The Raman spectra confirmed the presence of amorphous and crystalline structures by the existence of an intense D band separated from the G band, indicating early stages of crystallization. The interplanar distance corresponding to the graphite structures was determined by using HRTEM micrographs.
Keywords: Carbon films; Graphene; Graphite; Sputtered carbon